Influence of coating parameters on oxidation behavior of Cr-coated zirconium alloy for accident tolerant fuel claddings. (15th July 2022) - Kashkarov, E.B.; Sidelev, D.V.; Pushilina, N.S.; Yang, J.; Tang, C.; Steinbrueck, M.
Abstract: The Cr coatings (4.5–9.0 µm-thick) with porous/columnar and dense/columnar microstructure were deposited on Zr alloy. Oxidation was performed at 900, 1050, 1200 and 1400 °C in steam to define the role of coating microstructure and thickness on oxidation behavior of Cr-coated Zr alloy. The activation energy for chromium oxidation decreases from 249 to 124 kJ/mol when the coating microstructure changes from dense to porous. Both coatings types are consumed by Cr-Zr interdiffusion resulting in the similar thickness of residual Cr. The Cr-Zr interdiffusion can prevent forming the Cr oxide film and cause direct oxidation of the alloy at 1400 °C. Highlights: Effect of coating thickness on oxidation resistance of Cr-coated Zr alloy. Higher oxidation resistance of Zr alloy with dense Сr coatings. Сonsuming Cr coatings by oxidation in steam and Cr-Zr interdiffusion. Stabilization of α-Zr (O) phase slows down Cr-Zr interdiffusion.